Dizabilitatea ca factor de risc privind accesul la serviciile de educaţie - Manea, Livius (Calitatea Vieții, 2006)
This paper presents the relationship between the disability definitions, based on the individual (medical) or the social models’ perspectives, on the one hand, and the services provided to the disabled people, on the other hand. At the same time, it puts a spotlight on the complex relationships between disability, education and social exclusion. The paper refers to some examples which demonstrate that the segregated special education is not able to have a meaningful positive impact on disabled people’s integration and social inclusion. Although during the late decades there was an unfolding inclusion process of children with disabilities into ordinary schools, there are still some educators which call for segregated special education. The content of the paper includes some remarks about the changes in the field of special education, in Romania.